2008
DOI: 10.1165/rcmb.2008-0015rc
|View full text |Cite
|
Sign up to set email alerts
|

α1-Antitrypsin Inhibits the Activity of the Matriptase Catalytic Domain In Vitro

Abstract: Matriptase is a type II transmembrane protease that is characterized by an N-terminal transmembrane and multiple extracellular domains, in addition to the conserved extracellular serine protease catalytic domain. The expression pattern of matriptase suggests that this protease may play broad roles in the biology of surface lining epithelial cells. In this study we report that a 1 -antitrypsin (AAT), an endogenous inhibitor of serine proteases, inhibits the catalytic domain of human recombinant matriptase in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…In support of this hypothesis, recently, Tseng and colleagues (44) isolated A1AT/matriptase complexes from human milk that are resistant to dissociation in boiling SDS, suggesting that A1AT may bind to matriptase in an irreversible fashion. We also reported that native but not the inactivated A1AT inhibits the catalytic domain of matriptase with a second-order rate constant of 0.31 3 10 3 M 21 s 21 in vitro in an irreversible fashion (16). Other serine proteinase inhibitors, like aprotinin and nexin-1 (PN-1) have also been shown to inhibit the activity of matriptase, thereby decreasing ENaC currents.…”
Section: Discussionmentioning
confidence: 87%
“…In support of this hypothesis, recently, Tseng and colleagues (44) isolated A1AT/matriptase complexes from human milk that are resistant to dissociation in boiling SDS, suggesting that A1AT may bind to matriptase in an irreversible fashion. We also reported that native but not the inactivated A1AT inhibits the catalytic domain of matriptase with a second-order rate constant of 0.31 3 10 3 M 21 s 21 in vitro in an irreversible fashion (16). Other serine proteinase inhibitors, like aprotinin and nexin-1 (PN-1) have also been shown to inhibit the activity of matriptase, thereby decreasing ENaC currents.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, the absence of elastase had no effect on neutrophil recruitment (26), which supports our findings. Circulating AAT enters cells (27) and can act as an inhibitor for matriptase (28), caspases-1 and -3 (29,30), TNF-α-converting enzyme (31), and intracellular calpain I (32).…”
Section: Discussionmentioning
confidence: 99%
“…Protease inhibitor nexin 1, another member of the SERPIN family that inhibits matriptase (52,53), also inhibited Na 1 currents across human airway epithelial cells isolated from CF lungs (52). Based on Western blotting studies of surface proteins of ATII cells in culture and in situ, we conclude that IaI decreased ENaC activity by preventing membran-bound proteases from cleaving portions of the extracellular loops of a-and g-ENaC subunits, thereby inhibiting the activation of ENaC at the cell membrane of lung epithelial cells and oocytes.…”
Section: Original Researchmentioning
confidence: 99%